The change of tendencies in the German-Russian relations : The case of Ukrainian crisis - Oliichuk, Vitalii (2020)
Armed conflict in Eastern Ukraine created a security crisis in the EU and escalated the German-Russia relations that were in a cool-off period for a long time. The analysis of German actions is an essential aspect in understanding of the Ukrainian crisis, as Germany (being a leader in its settlement) strongly influences the course of events not only in Ukraine but also in Europe.